Population Aging in Japan : Demographic Shock and Fiscal Sustainability - Muhleisen, Martin (IMF Working Papers; Working Paper ;, 2001)
The paper develops a general equilibrium framework to examine the economic implications of population aging in Japan. Particular attention is paid to aggregate saving behavior which is modeled on the basis of empirical age-earnings profiles using a life-cycle approach. The paper's objectives are to (i) estimate the output loss caused by demographic changes and assess the impact of aging on Japan's government finances; and (ii) compare fiscal policy options with respect to their effects on output growth and economic welfare. The paper develops a general equilibrium framework to examine the economic implications of population aging in Japan. Particular attention is paid to aggregate saving behavior which is modeled on the basis of empirical age-earnings profiles using a life-cycle approach. The paper's objectives are to (i) estimate the output loss caused by demographic changes and assess the impact of aging on Japan's government finances; and (ii) compare fiscal policy options with respect to their effects on output growth and economic welfare. The paper develops a general equilibrium framework to examine the economic implications of population aging in Japan. Particular attention is paid to aggregate saving behavior which is modeled on the basis of empirical age-earnings profiles using a life-cycle approach. The paper's objectives are to (i) estimate the output loss caused by demographic changes and assess the impact of aging on Japan's government finances; and (ii) compare fiscal policy options with respect to their effects on output growth and economic welfare.